The influence of accountability, transparency, participation, and characteristics of satya on the management of village funds - Gede Sanjaya Adi Putra; Gde Deny Larasdiputra (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
This study aims to determine the effect of accountability, transparency, and community participation on the management of village funds with Satya as a moderating variable. The population in this study was the people of Sading Village with the following criteria: village officials (village government organizations) and hamlet representatives (banjar adat) who were involved in village fund management meetings with a sample of 82 people. The theory used in this research is Stewardship Theory and agency theory. The data analysis technique used in this study is Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). The results of the study stated that H1, H2, H3, and H6 were accepted while H4 and H5 were rejected. This shows that accountability, transparency, and participation have a positive effect on the management of village funds. The nature of Satya is not able to moderate the effect of Accountability and Transparency on management and villages. However, the nature of Satya is able to moderate the positive influence of community participation on management and villages.